The cosmic dance : finding patterns and pathways in a chaotic universe - Ellcock, Stephen (New York, New York : Thames & Hudson, 2022)
In 'The Cosmic Dance', renowned image alchemist Stephen Ellcock presents a pan-global collection of remarkable, arresting and surprising images drawn from the entire history of art to explore the ancient belief that the cosmos is reflected in all living things. Organized thematically, the visual journey begins with the microscopic, the particulate and the elemental; then explores the human body as a cosmos in miniature, the beauty of divine proportions and our search for spiritual enlightenment; before finally revelling in the colossal, the celestial and the infinite. An eloquent introduction provides an overview of the central themes and expert commentaries introduce each section. Detailed panels provide bitesize information on key concepts and key thinkers - from the four elements to Cosmic Man and from the moebius strip to the Mandelbrot set - while thought-provoking quotations from philosophers, writers, artists and scientists interspersed throughout the artworks prompt a closer, more personal engagement with the images. This stunning treasury of artworks provides the perfect guide to a deeper contemplation of the world around us, allowing readers, in the words of William Blake, to 'see a world in a grain of sand, and a heaven in a wild flower, hold infinity in the palm of your hand, and eternity in an hour'.--
In search of nirvana. The living earth ; Forces of creation and destruction ; Alchemy ; The properties of beasts, bestiaries, the hierarchy of beasts ; Visions of Eden, earthly paradise, the diorama of life ; Heaven, hell and the afterlife ; Angels and demons, gods and goddesses, immortals, divine beings ; Heavenly messengers ; Supernatural beings ; Enlightened souls ; Fallen angels ; Powers of darkness ; Spiritual void -- And so to infinity. The macrocosmos ; Metaphysics ; Signs and wonders ; Mapping the universe ; Exploring the cosmos ; The runaway universe ; The celestial wheel ; The zodiac ; Terrestrial and sidereal calendars ; Measuring time ; Models of infinity ; Visions of eternity ; Cosmology ; Celestial mapping ; Perpetual motion.
boek